Decreased expression of EphA5 is associated with Fuhrman nuclear grade and pathological tumour stage in ccRCC. Issue 1 (19th April 2017) - Wang, Xiaolin; Xu, Haifei; Wu, Zhijun; Chen, Xiao; Wang, Jiandong
Summary: The incidence of renal cell carcinoma is increasing all over the world. The molecular mechanisms for tumorigenesis, progression and prognosis are still unknown. The erythropoietin‐producing hepatoma amplified sequence (Eph) receptors have been reported to be expressed aberrantly in many types of human cancers and in particular EphA5 may play a role in certain human cancers. In this study, a set of clear cell renal cell carcinoma (ccRCC) tissues were subjected to immunohistochemistry. The relationship between EphA5 protein expression and clinicopathological parameters was statistically analysed. Our data show that EphA5 protein was negatively (0) or weakly (1+) expressed in 48 of 78 (61.5%), moderately (2+) expressed in 15 of 78 (19.2%) and strongly (3+) expressed in 15 of 78 (19.2%) tumour samples of ccRCC. Decreased expression of EphA5 was detected more often in females than in males ( P = 0.017, r s = −0.267). Expression of EphA5 was related negatively to Fuhrman grade ( P = 0.013, r s = −0.279) and pathological tumour stage pT ( P = 0.003, r s = −0.334). No relation between the expression of EphA5 and age of patients was found ( P = 0.107, r s = 0.184). Fuhrman grade and pT stage are the most important factors used in prognosis of ccRCC. Hence this study may provide a new and useful prognostic marker in the clinical practice of ccRCC.